2022
DOI: 10.1007/s11356-022-20447-z
|View full text |Cite
|
Sign up to set email alerts
|

Ambient air pollutants increase the risk of immunoglobulin E–mediated allergic diseases: a systematic review and meta-analysis

Abstract: Immunoglobulin E (IgE)-mediated allergic diseases, including eczema, atopic dermatitis (AD), and allergic rhinitis (AR), have increased prevalence in recent decades. Recent studies have proved that environmental pollution might have correlations with IgE-mediated allergic diseases, but existing research findings were controversial. Thus, we performed a comprehensive meta-analysis from published observational studies to evaluate the risk of long-term and short-term exposure to air pollutants on eczema, AD, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 87 publications
(39 reference statements)
0
11
0
1
Order By: Relevance
“…Air pollution may be related to the development and exacerbation of AD [ 30 , 31 , 32 , 33 ]. Woo et al [ 34 ] reported that PM 10 exposure induces and aggravates skin inflammation via the differential expression of genes controlling skin barrier integrity and immune response in ovalbumin (OVA)-treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…Air pollution may be related to the development and exacerbation of AD [ 30 , 31 , 32 , 33 ]. Woo et al [ 34 ] reported that PM 10 exposure induces and aggravates skin inflammation via the differential expression of genes controlling skin barrier integrity and immune response in ovalbumin (OVA)-treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…This study by Wang et al [11] observed a significant association between long term exposure to PM 2.5 , NO 2 , and CO and the development of allergic rhinitis (AR) and atopic dermatitis (AD). The observation that an increase in NO 2 and CO exposure was associated with a significant elevation in immunoglobulin E (IgE) and subsequent allergic diseases, suggested a potential association with allergic asthma as well [11]. The potential risk of outdoor air pollution is enhanced given the significant contribution of outdoor air pollution to indoor air quality.…”
Section: Outdoor Air Pollution Components and Asthmamentioning
confidence: 96%
“…In urban areas, traffic related air pollution (TRAP) is a particular focus. A recent systematic review and meta-analysis evaluated ambient air pollutants and the risk of immunoglobulin E-mediated allergic disease [11]. This study by Wang et al [11] observed a significant association between long term exposure to PM 2.5 , NO 2 , and CO and the development of allergic rhinitis (AR) and atopic dermatitis (AD).…”
Section: Outdoor Air Pollution Components and Asthmamentioning
confidence: 99%
“…大気中に浮遊する粒径が 2.5 µm 以下の粒子は, 呼吸器の奥深く肺胞まで到達し,血中への移行を 通じた重篤な健康被害をもたらす.例えば,慢 性 閉 塞 性 肺 疾 患(chronic obstructive pulmonary disease: COPD) 1) などの呼吸器系,院外心原性心停止 (out-of-hospital cardiac arrest: OHCA) 2,3) などの循環 器系及びアレルギー性鼻炎 4) などの免疫系,更に肺 がん 5) のような発がん性など多くの健康影響 [6][7][8] が 報告されている.大気粒子状物質は,発生源から直 接排出される一次粒子[有機炭素(有機化合物) ,元 素状炭素,無機元素(金属)など]と排出時にはガ ス状物質であるが,それらの化学反応により粒子化 される二次生成粒子(硫酸塩,硝酸塩,アンモニウ ム塩,低分子有機酸 9) など)が知られている. [10][11][12] 浮 遊 粒 子 状 物 質(suspended particulate matter: 18,19) その結果,硫酸アンモニウム は,細胞障害性を誘発し, 18) また,細胞障害を引き 起こさない条件で C57 細胞の脱顆粒を誘発,又は thapsigargin の刺激による脱顆粒反応を増強するこ とを報告した. 19) さらに,それらに影響するイオン は,硫酸アンモニウムの構成成分のうち,硫酸イオ ンではなくアンモニウムイオンであることを明らか にした. 18,19) ついで,われわれは中国大陸から PM 2. の培養条件を一部改良して行った.すなわち, ( 1)…”
Section: 緒 言unclassified